Enzymatic production of clickable and PEGylated recombinant polyhydroxyalkanoates. Issue 22 (1st November 2017) - Vastano, M.; Pellis, A.; Immirzi, B.; Dal Poggetto, G.; Malinconico, M.; Sannia, G.; Guebitz, G. M.; Pezzella, C.
Abstract : Polyhydroxyalkanoates (PHAs) are microbial polyesters attracting great attention while further functionalisation could widen their applicability. Abstract : Polyhydroxyalkanoates (PHAs) are microbial polyesters attracting great attention while further functionalisation could widen their applicability. Various Escherichia coli based production systems using the PHA biosynthetic operon from Bacillus cereus 6E/2 were designed to enhance the accumulation of PHAs with high medium chain length moieties. Media optimization and system engineering were applied, yielding the production of PHAs up to 260 mg L −1 . Polymer characterization revealed a low grade of crystallinity and remarkable hydrophobic features. For further functionalization, a novel enzyme based strategy was developed. Lipase B from Candida antarctica (CaLB) was used to catalyze the terminal coupling of PHAs with: (i) dimethyl itaconate (DMI) in order to introduce reactive side chain vinyl moieties for the easy coupling of functional molecules and/or (ii) biocompatible polyethylene glycol (PEG) to tune polymer hydrophilicity. The functionalized DMI–PHA, PEG–PHA and PEG–DMI–PHA polymers obtained and characterised by NMR, GPC, FT-IR, and WCA in this study open new perspectives on the use of PHAs as biodegradable and biocompatible materials of choice for biomedical applications.